ENHANCING COGNITIVE ABILITIES OF STUDENTS THROUGH DIGITALIZATION IN HIGHER EDUCATION (American Journal of Interdisciplinary Research and Development, 2023)
This article explores the potential of digitalization in higher education to enhance the cognitive abilities of students. It discusses the various ways in which digital tools and technologies can be used to promote critical thinking, problem-solving, and creativity among students. The article also highlights the challenges and limitations of digitalization in higher education and provides recommendations for educators to effectively integrate digital tools into their teaching practices.